HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG GIZI DAN POLA MAKAN BALITA DENGAN STATUS GIZI BALITA DI DESA BRINGINSARI KECAMATAN SUKOREJO KABUPATEN KENDAL - Rohana, Nana (Jurnal Ilmu dan Teknologi Kesehatan, 2012)
Relationship of Knowledge on Nutrition And Diet Children With Nutritional Status of Children In The Village District District Sukorejo Bringinsari Kendal This study aimed to determine the relationship of mothers knowledge about nutrition, diet with nutritional status of children under five in the Village District Sukorejo Bringinsari Kendal. This study uses a quantitative method with cross sectional approach. Sampling some 68 people with proportionate random sampling technique. The instruments used were questionnaires, forms recall and hanging scales. The results of this study are: indicates the level of knowledge of mothers in the village of mostly poor Bringinsari by 41 people (60.29%), diet toddler in the village of mostly poor Bringinsari of 35 children (51.48%), nutritional status of children The village Bringinsari majority of malnutrition by 39 children (57.35%). There is a relationship between mothers knowledge about nutrition and diet toddlers (p value 0.000) under five (p value 0.001), there is a relationship between mothers knowledge about nutrition and nutritional status of children (p value 0.003). The need for monitoring the nutritional status of infants at regular intervals so that the state of nutritional status can be determined and immediate response in case of a decrease in nutritional status. Hubungan Tingkat Pengetahuan Ibu (Nana Rohana)                                                           1 Keywords: Knowledge mothers about infant nutrition, infant diet, nutritional status of children